A model for droplet heating and evaporation of water-in-oil emulsified fuel. (15th April 2020) - Shen, Shiquan; Che, Zhizhao; Wang, Tianyou; Yue, Zongyu; Sun, Kai; Som, Sibendu
Highlights: A model for droplet heating and evaporation of water-in-oil emulsified fuel is developed. Deactivation temperature of surfactant is selected as a criterion for water coalescence. The model can well predict the droplet heating and evaporation process. Over-high heating temperature is not favorable for the occurrence of micro-explosion. Abstract: Water-in-oil (W/O) emulsified fuel is a promising alternative fuel by inducing flash boiling of water at high temperature that can improve the atomization of fuel spray. The heating and evaporation process of emulsified fuel droplet is affected by the diffusion and coalescence of small dispersed water droplets in oil during the heating. In this study, a model is developed for the droplet heating and evaporation of W/O emulsified fuel with these key physics considered. The diffusivity of dispersed water droplets in oil is calculated using the Stokes-Einstein equation. The deactivation temperature of surfactant is selected as a criterion for the water coalescence since the water coalescence is due to the deactivation of surfactant. The process of water coalescence is simplified that the dispersed water droplets coalesce into one single water sub-droplet at the center of the oil droplet instantly as the droplet temperature reaches the deactivation temperature of surfactant. The model is validated against experimental data of single droplet under different heating temperatures, surfactant concentrations, and sizes of dispersed water droplets. Based on the proposed model, the effects of fuel properties and heating conditions on the droplet heating and evaporation are analyzed.